2019
DOI: 10.1115/1.4042059
|View full text |Cite
|
Sign up to set email alerts
|

Heat Transfer Model of a 50 kW Solar Receiver–Reactor for Thermochemical Redox Cycling Using Cerium Dioxide

Abstract: This work reports on the development of a transient heat transfer model of a solar receiver–reactor designed for thermochemical redox cycling by temperature and pressure swing of pure cerium dioxide in the form of a reticulated porous ceramic (RPC). In the first, endothermal step, the cerium dioxide RPC is directly heated with concentrated solar radiation to 1500 °C while under vacuum pressure of less than 10 mbar, thereby releasing oxygen from its crystal lattice. In the subsequent, exothermic step, the react… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 51 publications
0
16
0
Order By: Relevance
“…Radiative heat transport within the RPC can be calculated using its effective radiative properties, e.g., effective extinction coefficient and effective scattering phase function, which in turn can be computed via pore‐level Monte Carlo (MC) simulation and other statistical approaches . When the macro‐porosity of the RPC is increased, its optical thickness decreases, radiation penetrates more deeply, which can improve the solar‐to‐fuel energy conversion efficiency to some extent, provided the apparent density—defined as the ceria mass per unit volume of the porous structure—is not reduced. On the other hand, the maximum pore diameter and/or minimum strut thickness of the RPC fabricated by the replica method with polyurethane foams is limited due to its mechanical stability …”
Section: Introductionmentioning
confidence: 99%
“…Radiative heat transport within the RPC can be calculated using its effective radiative properties, e.g., effective extinction coefficient and effective scattering phase function, which in turn can be computed via pore‐level Monte Carlo (MC) simulation and other statistical approaches . When the macro‐porosity of the RPC is increased, its optical thickness decreases, radiation penetrates more deeply, which can improve the solar‐to‐fuel energy conversion efficiency to some extent, provided the apparent density—defined as the ceria mass per unit volume of the porous structure—is not reduced. On the other hand, the maximum pore diameter and/or minimum strut thickness of the RPC fabricated by the replica method with polyurethane foams is limited due to its mechanical stability …”
Section: Introductionmentioning
confidence: 99%
“…Solar reactors for effecting this cycle include cavity receivers with rotating or stationary structures, [48][49][50][51][52][53][54][55][56][57][58][59][60] glass dome reactors, [61] aerosol flow reactors, [62] particle reactors, [63] and moving and fluidized bed reactors. [64,65] The most promising receiver/reactor designed to date is the cavity receiver containing a reticulated porous ceramic (RPC) foam made of pure CeO 2 .…”
Section: Resultsmentioning
confidence: 99%
“…[64,65] The most promising receiver/reactor designed to date is the cavity receiver containing a reticulated porous ceramic (RPC) foam made of pure CeO 2 . [51][52][53][54][55][56][57][58][59] A schematic of the receiver reactor is proposed in Figure 1. The RPC was directly exposed to concentrated thermal radiation at mean solar flux concentration ratios of up to 3015 suns.…”
Section: Resultsmentioning
confidence: 99%
“…It was proved that the model has a higher agreement with the model of Zinkevich et al [32]. Zoller et al [26] used the thermodynamic equilibrium model to simulate a 50kW solar receiver-reactor, which obtained the solar-to-fuel efficiency larger than 10% with dual-scale reticulated porous ceramic. The most basic chemical kinetics reaction model is based on the Arrhenius equation proposed by Ishida et al [33].…”
Section: Introductionmentioning
confidence: 96%
“…The fuel production rate was enhanced by as much as 260% and 175% compared with traditional low porosity ceria and non-ordered mesoporous ceria. Oliveira et al [26] further studied the 3DOM ceria structure for solar thermochemical CO2 splitting in a tubular reactor. The result showed that the maximum fuel production rate is three times higher than the dual-scale porosity ceria reticulated porous foam.…”
Section: Introductionmentioning
confidence: 99%